APLIKASI AKAD MUDARABAH DALAM PRODUK TABUNGAN HAJI DAN UMROH (TAHAROH) DAN KEFAHAMAN PELANGGAN TERHADAPNYA: KAJIAN DI BANK PEMBIAYAAN RAKYAT SYARIAH HARTA INSAN KARIMAH (BPRS HIK) BEKASI, INDONESIA: The Application of Mudarabah Contract in Tabungan Haji dan Umroh (TAHAROH) Product and Customers’ Understanding Against It: A Case Study at Bank Pembiayaan Rakyat Syariah Harta Insan Karimah (BPRS HIK) Bekasi, Indonesia - Kurniawan, Taufiq; Ab Rahman, Asmak (Jurnal Syariah, 2014)
Mudarabah is one of the partnership agreements in Islam. The contract is valid if all the rules and conditions of the contract are fulfilled. Muslims in Indonesia do not have special fund for savings to perform hajj. Thus, Bank Pembiayaan Rakyat Syariah/Harta Insan Karimah (BPRS HIK) Bekasi introduced a fundraising product using the mudarabah concept, where the customers could only withdraw their savings when it has reached the minimum cost to perform the hajj. The product is known as TAHAROH (Tabungan Haji & Umroh). This research is conducted to investigate how the mudarabah contract has been used in this product. The data was collected using interview with the person in charge at the BPRS HIK and also the customers who are saving in this fund for the purpose of performing hajj. The study found that the bank manage the mudarabah fund through few mechanism to avoid risk of loss to the customers mudarabah fund, since under the mudarabah contract the fund cannot be guaranteed from losses and the customers also do not expect their saving to perform hajj expose to losses.